The FGF-AKT pathway is necessary for cardiomyocyte survival for heart regeneration in zebrafish - Tahara, Naoyuki (Dev Biol, 2021)
Zebrafish have a remarkable ability to regenerate the myocardium after injury by proliferation of pre-existing cardiomyocytes. Fibroblast growth factor (FGF) signaling is known to play a critical role in zebrafish heart regeneration through promotion of neovascularization of the regenerating myocardium. Here, we define an additional function of FGF signaling in the zebrafish myocardium after injury. We find that FGF signaling is active in a small fraction of cardiomyocytes before injury, and that the number of FGF signaling-positive cardiomyocytes increases after amputation-induced injury. We show that ERK phosphorylation is prominent in endothelial cells, but not in cardiomyocytes. In contrast, basal levels of phospho-AKT positive cardiomyocytes are detected before injury, and the ratio of phosphorylated AKT-positive cardiomyocytes increases after injury, indicating a role of AKT signaling in cardiomyocytes following injury. Inhibition of FGF signaling reduced the number of phosphorylated AKT-positive cardiomyocytes and increased cardiomyocyte death without injury. Heart injury did not induce cardiomyocyte death; however, heart injury in combination with inhibition of FGF signaling caused significant increase in cardiomyocyte death. Pharmacological inhibition of AKT signaling after heart injury also caused increased cardiomyocyte death. Our data support the idea that FGF-AKT signaling-dependent cardiomyocyte survival is necessary for subsequent heart regeneration.